Um estudo sobre a insolvência das operadoras de planos de saúde - Viana, Andson de Freitas (2012)
In the 1990s there were several changes in the health sector in Brazil, one of the most important, the change in the law that regulates insurance carriers and plans for the risks to their health. This sector is becoming increasingly concentrated with an output greater than the entry of new firms. It is important to investigate this case, what factors contribute to a carrier's plan does not sustain the market. What are the signs (variables) visible in the accounts of those who anticipate insolvency? To answer this question, this paper uses a multivariate logit model for the probability of insolvency, where the main financial indicators are cofactors of companies drawn from the most current database of the National Health Insurance. In addition to these indicators, also investigated whether the type of health insurance carrier or the same site of action may also contribute to the risk of insolvency. As a result it was found that the type carrier and the region near each have no correlation in the level of OPS insolvency. So expected economic indicators of financial indebtedness (CT / CP and ENDIV) and receiving (PMCR) were the most important in predicting insolvency of companies in a subsequent period.